Safety at home - Raatma, Lucia (Mankato, Minn. : Bridgestone Books, 1999)
Explains how to prevent accidents around the home and deal with emergencies, covering such topics as electricity, medicines, and fires.
Includes bibliographical references (p. 24) and index.
Keywords: Home accidents -- Prevention -- Juvenile literature; Safety education -- Juvenile literature; Safety